The predominant pedagogical practices in the training of Region VI national NAMCYA winners, 1974-2005 - Bebit, Erlinda Ventilacion (2008)
The findings of this study may provide current and future mentors with insights and options in preparing NAMCYA finalists/ contestants from their respective regions. the results may help build the trainers' confidence in solving training-related problems. School administrators may be guided in the selection of teacher-trainers and participants. Lastly, this study could imply the amount and extent of support that may be required by such training.